Extended-Spectrum Beta-Lactamase Producing-Escherichia coli Isolated From Irrigation Waters and Produce in Ecuador - Montero, Lorena; Irazabal, Jorge; Cardenas, Paul; Graham, Jay P.; Trueba, Gabriel (Frontiers in Microbiology, 2021)
In cities across the globe, the majority of wastewater – consisting of drug-resistant and pathogenic bacteria among other contaminants – is released into streams untreated. This water is often subsequently used for irrigation of pastures and produce. This use of wastewater-contaminated streams allows antibiotic-resistant bacteria to potentially cycle back to humans through agricultural products. In this study, we investigated the prevalence of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli isolated from produce and irrigation water across 17 provinces of Ecuador. A total of 117 vegetable samples, 119 fruit samples, and 38 irrigation water samples were analyzed. Results showed that 11% of the samples were positive for E. coli including 11 irrigation water samples (29%), 13 vegetables samples (11%), and 11 fruits (9%). Among the 165 E. coli isolates cultured, 96 (58%) had the extended-spectrum beta-lactamase (ESBL) phenotype, and 58% of ESBL producing E. coli came from irrigation water samples, 11% from vegetables, and 30% from fruits. The CTX-M gene was the most frequently found gene associated with the ESBL phenotype, and the allelic variants of this gene coincided with those previously reported in bacteria associated with nosocomial infections in Ecuador. This report provides evidence of the potential role of wastewater in the growing antimicrobial resistance crisis in Ecuador.